Sepsis-Associated DIC with Decreased Levels of Antithrombin and Fibrinogen is the Target for Combination Therapy with Thrombomodulin Alfa and Antithrombin - Wada, Hideo; Kawasugi, Kazuo; Honda, Goichi; Kawano, Noriaki; Uchiyama, Toshimasa; Madoiwa, Seiji; Takezako, Naoki; Suzuki, Kei; Seki, Yoshinobu; Ikezoe, Takayuki; Iba, Toshiaki; Okamoto, Kohji (TH Open, 2023)
Background Disseminated intravascular coagulation (DIC) is not a homogeneous condition, but rather includes heterogeneous conditions, and its pathophysiology and outcome vary considerably depending on the background. Although anticoagulant therapy is expected to be of benefit in the treatment of DIC, previous studies have suggested that the benefits are limited only to a specific subtype.Objects The purpose of this study was to identify the group that would benefit from combination therapy using thrombomodulin/antithrombin.Methods The data from 2,839 patients registered in the postmarketing surveillance of thrombomodulin were evaluated. The patients were divided into four groups depending on antithrombin and fibrinogen levels, and the additive effects of antithrombin on thrombomodulin were examined in the groups.Results The DIC score, Sequential Organ Failure Assessment score, and mortality were significantly higher in the DIC group with low-antithrombin/low-fibrinogen than in the DIC groups without either low antithrombin or low fibrinogen. The survival curve was significantly higher in DIC patients with combination therapy than in patients treated with thrombomodulin monotherapy, but this effect was seen only in patients with infection-based DIC.Conclusion DIC patients with low-antithrombin/low-fibrinogen risk poor outcomes, but they can be the target of combination therapy with antithrombin and thrombomodulin as long as the DIC is due to infection.
Keywords: thrombomodulin; antithrombin; fibrinogen; disseminated intravascular coagulation; sepsis